Current opinion within the UK arboricultural industry on the management of bark-included junctions in trees. Issue 1 (2nd January 2019) - Slater, Duncan
ABSTRACT: Sharing practice amongst arboriculturists is potentially a very valuable process for identifying commonalities in approaches to tree management and to identify where further research is needed. In the particular case of bark-included junctions (a common structural flaw occurring in a wide range of tree species), a questionnaire was launched at eleven UK-based training workshops in 2016. The questionnaire covered theories and practices in relation to how bark-included junctions and natural braces are managed in the UK. The questionnaire received 348 responses, with a total of 6, 635 years of arboricultural experience. Respondents consistently identified that normally formed branch junctions are rarely seen to fail but bark-included junctions do so frequently; that failure of bark-included junctions is more commonly caused by tension over torsion; and that most UK practitioners prefer to prune to lessen the likelihood of failure of a bark-included junction rather than installing an artificial brace. Responses highlighted areas of uncertainty, including the main cause of bark-inclusion failures and the importance of natural braces to the structural integrity of trees. It also highlighted the need for further practical experimentation upon bark-included junctions at various stages of bulging and is considered a key research area to better inform risk management decisions.